Non-hematopoietic roles of erythropoietin in inflammation and metabolic disorders - Sugimoto, Satoru; Goda, Takeshi (Frontiers in Pharmacology, 2025)
Erythropoietin (EPO), a glycoprotein hormone primarily produced by the kidneys, is essential for erythropoiesis. Beyond its well-established hematopoietic function, EPO has emerged as a regulator of metabolic inflammation. Obesity-induced chronic inflammation underlies insulin resistance, a key driver of metabolic disorders such as type 2 diabetes mellitus (T2DM) and metabolic dysfunction-associated steatohepatitis (MASH). Recent evidence shows EPO exerts anti-inflammatory effects in insulin-sensitive tissues, thereby improving insulin sensitivity in the context of obesity. Although EPO is clinically approved for treating anemia in both neonates and adults, further evaluation is needed to establish its safety and tolerability when repurposed for metabolic indications across these populations. Nevertheless, to overcome the hematopoietic side effects of native EPO, researchers have developed non-hematopoietic analogs with selective tissue-protective actions. These analogs are currently under investigation and have shown therapeutic potential without erythropoietic side effects. This review summarizes the anti-inflammatory roles of EPO in obesity-related metabolic dysfunction, particularly in white adipose tissue (WAT) and the liver, and discusses the therapeutic potential of non-hematopoietic EPO analogs.